Safety of feedback discrete event systems with unknown controllers - França, Tiago Cardoso (2017)
Present a safety device that deals with the problem of cyberattacks and incorrect implementation of controllers on discrete event systems. A cyber-attack modifies the behavior of the system, and may lead it to unsafe states, i.e., states that may cause damage to the system components or its operator. In addition, an incorrect implementation or design of controllers may also lead the system to unsafe states. In this work, we assume those changes in the implemented logic of the controller, which modify the behavior of the system, and thus we assume the controller to be unknown. The safety device is designed to prevent the modified controlled plant from reaching unsafe states. However, in some cases, the device may block safe behaviors of the system. For this reason, we present an algorithm to verify the safety level of the interaction between the device and the plant. The results shown in this work are illustrated by a case study in a mechatronic plant in the Control and Automation Laboratory at the Federal University of Rio de Janeiro.